Dams in Africa : an inter-disciplinary study of man-made lakes in Africa - Rubin, Neville; Warren, William M. (London : Frank Cass & Co. Ltd., 1968)
This volume was originated in a seminar that was conducted at a school of Oriental and African studies of the University of London during a session. It represents part of a continuing process which seek to involve the different departments of the school concerned with African studies in the advancements of inter-disciplinary work in this area.
Includes bibliographical footnotes.
hza 28/01/2019
Loans
Keywords: Dams; Economic history; Africa